The interaction effects of polycyclic aromatic hydrocarbons exposure and TERT- CLPTM1L variants on longitudinal telomere length shortening: A prospective cohort study. (November 2018) - Fu, Wenshan; Chen, Zhuowang; Bai, Yansen; Wu, Xiulong; Li, Guyanan; Chen, Weilin; Wang, Gege; Wang, Suhan; Li, Xiaoliang; He, Meian; Zhang, Xiaomin; Wu, Tangchun; et al.
Abstract: Telomere length (TL) is an index of cellular aging and can predict the incidences of many age-related diseases. Change of TL might be affected by environmental pollution and individual's genetic background. In this cohort study, we aimed to evaluate the associations between polycyclic aromatic hydrocarbons (PAHs) exposure and longitudinal TL shortening, and investigate whether genetic variations in TERT-CLPTM1L can modify these associations. We measured the baseline concentrations of twelve urinary PAH metabolites and genotyped six variants at TERT-CLPTM1L among 1243 coke-oven workers. The relative leukocyte TL was detected in both baseline and follow-up (4 years later) visits. The TL shortening were estimated by TL decline and TL ratio. We found that the urinary level of 1-hydroxypyrene (1-OHP) had significant dose-response relationships with increased TL decline [β(95%CI) = 0.078(0.023, 0.133), P = 0.005] and TL ratio [β(95%CI) = 0.096(0.037, 0.155), P = 0.002]. Besides, urinary 1-hydroxynaphthalene (1-OHNa) was marginally dose-related with elevated TL decline [β(95%CI) = 0.053(-0.001, 0.107), P = 0.055] and TL ratio [β(95%CI) = 0.057(-0.002, 0.116), P = 0.058]. Analyses of TERT-CLPTM1L variants showed that the rs401681 and rs465498 could modify the effect of 1-OHP on increasing TL decline ( P interaction = 0.012 and 0.035, respectively) and TL ratio ( P interaction = 0.014 and 0.067, respectively), which were pronounced among rs401681TT and rs465498CC carriers, but not seen among rs401681TC + CC and rs465498CT + TT carriers. In conclusion, elevated exposure to PAHs can accelerate the TL shortening and this effect can be modified by TERT-CLPTM1L variants. These results may add potential evidence for gene-environment interactions on dynamic changes of telomere length. Further studies are warranted to validate these findings and uncover the underlying mechanisms. Graphical abstract: Image 1 Highlights: A cohort design to study the PAHs-gene interactions on dynamic telomere shortening. Elevated exposure to PAHs could accelerate 4-year telomere shortening. Telomere shortening varies in people with distinct rs465498 genotypes. TERT-CLPTM1L variants interact with PAHs to accelerate 4-year telomere shortening. Abstract : PAHs exposure can interact with TERT-CLPTM1L variants to accelerate longitudinal telomere shortening.